IMPLEMENTASI NILAI GOTONG ROYONG MASYARAKAT DESA KENANGA PADA TRADISI UNJUNG-UNJUNGAN : Studi Etnografi pada Tradisi Unjung-Unjungan di Desa Kenanga Kecamatan Sindang Kabupaten Indramayu - Suwandi, - (2019)
This research is a study that examines the existence of mutual cooperation in rural communities in the implementation of tradition. The focus of this research is to explain the implementation of gotong royong values carried out by the people of Kenanga village on the tradition of unjung-unjungan. The purpose of this study is to describe the procession of the implementation of the unjung-unjungan tradition in Kebuyutan Canting, and obtain descriptive conclusions regarding how the community in Kenanga Village, Sindang Subdistrict, Indramayu District, implements the gotong royong value in the implementation of the unjung-unjungan tradition in Kebuyutan Canting. The research method used to study scientifically the implementation of the gotong royong value in the community of Kenanga village is the ethnographic study research method. While the data needed in this study was obtained from interview with the informants, directly observing the process of implementing tradition in Kebuyutan Canting, documentation and study of relevant literacy. The results showed that the implementation of gotong royong values to the community in Kenanga Village, Sindang District, Indramayu Regency. In the implementation of the unjung-unjungan tradition manifests in the form of activities and material contributions. Some gotong royong activities in the implementation of the unjung-unjungan tradition in Kebuyutan Canting, which is: 1) mupul activities, are fundraising activities carried out by volunteers; 2) melekan activities; 3) betek activities; 4) beberes kebuyutan activities; and 5) numpeng activities carried out by local people. While, some implementations of the gotong royong value in the form of material donations, among others: 1) making food in the form of tumpeng, panjang, fruits and market snacks (bread, cakes, instant noodles, etc.) carried out by local peoples; 2) voluntary contributions in the form of cash from the Kenanga village community as a whole; and 3) contribution of leasing of supporting facilities and infrastructure in the implementation of the tradition of the bridge. Keywords: values, gotong royong, rural communities, traditions